Evaluasi Perbandingan Anggaran Biaya Konstruksi Antara Metode SNI Dengan Metode Kontraktor - Dwiky Suhermawan; Hammam Rofiqi Agustapraja (Universitas Negeri Gorontalo, 2023)
It is very important to understand the more favorable cost estimation comparison between SNI 2022 and the Contractor, because this information is used as a reference in calculating contractors and preventing losses. The purpose of this research is to identify the differences and similarities between the contractor calculation method and SNI 2022, and also to find out which budgeting method is effective. This study uses the analysis method of SNI Number 1 of 2022 and the contractor calculation analysis method. Based on the research results, the effective price is Rp. 2,988,685,140.71 which is calculated based on the contractor's analysis. This price is 14.59% efficient from the price calculated based on the SNI 2022 analysis. Meanwhile the price set based on the SNI 2022 analysis is Rp. 3,424,599,423.59. From the results of the cost comparison between the 2016 SNI method and the contractor, it is known that the difference in costs is around Rp. 435,914,282.88. Based on the research results, the effective budget is calculated based on the analysis of contractor calculations.